Clinical characteristics of hypertrophic cranial pachymeningitis in granulomatosis with polyangiitis: a retrospective single-center study in China - Chen, Yiran; Gou, Lijuan; Wang, Li; Qian, Min; Wu, Qingjun; Zheng, Wenjie; Li, Mengtao; Zeng, Xiaofeng; Zhang, Fengchun (Arthritis research & therapy, 2024)
Hypertrophic cranial pachymeningitis (HCP) is uncommon but a poorly understood complication of granulomatosis with polyangiitis (GPA). We conducted this retrospective study to elucidate the clinical characteristics and factors independently associated with granulomatosis with polyangiitis (GPA) complicated by hypertrophic cranial pachymeningitis (HCP) in China. We collected the medical records of 78 patients diagnosed with GPA who were admitted to the inpatient department of Peking Union Medical College Hospital between January 2003 and September 2021. Clinical features, laboratory and radiological findings, and Birmingham Vasculitis Activity Scores (excluding meningitis score) were recorded. A binary logistic regression analysis was performed to analyze factors independently associated with GPA-related HCP. Headache (100%) and cranial nerve palsy (61.5%) were common manifestations of HCP. Compared to 52 GPA patients without HCP, 26 patients with HCP required more time from initial symptoms to diagnosis, with a lower ratio of pulmonary and renal involvement, a higher ratio of myeloperoxidase-antineutrophil cytoplasmic antibody (MPO-ANCA) positivity, conductive or sensorineural hearing loss, mastoiditis, and decreased vision or sudden visual loss. Binary logistic regression analysis indicated that proteinase 3-antineutrophil cytoplasmic antibody (PR3-ANCA) negativity (OR 10.698, p = 0.001), conductive or sensorineural hearing loss (OR 10.855, p = 0.005), and decreased vision or sudden visual loss (OR 8.647, p = 0.015) were significantly associated with GPA-related HCP. Of the 26 patients, 18 received methylprednisolone pulse treatment, and 18 received intrathecal injections of dexamethasone and methotrexate. HCP was a severe manifestation of GPA in our study. Independent factors associated with the occurrence of HCP in patients with GPA included PR3-ANCA negativity, conductive or sensorineural hearing loss, and decreased vision or sudden visual loss. Furthermore, GPA-related HCP was associated with higher disease activity, requiring more intensive treatments.